Investigating the Impact of Urbanization on Surface and Sub-Surface Water Flows and Statistical Change Detection in Water Cycle Over Two Decades - Sharma, Sheetal (Emerging Issues in Environment, Geography and Earth Science Vol. 5, 2023)
The chapter attempts to correlate and identify the periodic changes in the urban water cycle that have occurred throughout the urbanization of Bhopal City, India, during the previous twenty years and beyond. Several urban cities are facing water related problems in India and overseas. Urbanization is defined as the physical modification of landscapes that alters the natural regime of the environment surrounding it, resulting in further changes in the region's macro and micro climate. Water scarcity and urban flash floods are perennial issues in metropolitan settings. Studies have determined that land use, land cover, water extraction, and urban development are the causing factors of the hydrological cycle's impacted components, which include infiltration, runoff, and evaporation. The trend of urban development thus destabilizes water availability, water recharge, and the water cycle. The findings are based on GIS mapping of the research region from 1991 to 2009, which used a rational approach of runoff and recharge estimates, as well as a statistical analysis of related built-up areas. Changes in the natural route of drainages have also been discovered using GIS imagery during the last twenty years, which aids in observing the adaptation of natural systems to urban courses. The observations also reveal an intriguing relationship that can be exploited for future research and sustainable development.